Formação e consultoria colaborativa escolar para professores especializados de alunos com Transtorno do Espectro Autista - Pereira, Amanda Cristina dos Santos (Universidade Federal de São Carlos, 2025)
Considering the challenges in the schooling of students with Autism Spectrum Disorder (ASD) reported in the Brazilian scientific literature, the present study aimed to investigate the effects of teacher training procedures for educators working in inclusive regular education settings, across two separate studies. Study 1 aimed to design, implement, and evaluate the effects of an online, lecture-based training program for participants regarding basic theoretical knowledge of Behavior Analysis, specifically related to the management of challenging behaviors in students with ASD. An A-B-A experimental design was employed. The dependent variable was the participants' performance on theoretical questions about managing challenging behavior, while the independent variable was the training delivered by the researcher. Five teachers from a municipal school district in the interior of São Paulo state participated in this study. The data collection procedure comprised four stages conducted online and synchronously. The results indicated that the training increased participants’ theoretical repertoire and stimulated reflection on their educational practices, leading them to consider evidence-based practices grounded in Applied Behavior Analysis (ABA). Study 2 aimed to evaluate the effects of a collaborative consultation on the development of documents related to the schooling of students with ASD, focusing on ABA-based practices within the regular school context. The specific objectives were: (a) to identify challenges in implementing the collaborative consultation for intervention planning through the development of the following documents: Assessment Report, Individualized Education Plan (IEP), and Challenging Behavior Management Plan in the School Context; and (b) to assess participants’ perceptions regarding the importance and feasibility of implementing these documents in their school settings. This was a collaborative research study, involving three teachers. The dependent variable was the behavior of one participant in the development of the Assessment Report, IEP, and Challenging Behavior Management Plan for their students, and the independent variable was the collaborative consultation with the researcher. The data collection procedure included nine stages, and the consultation sessions were conducted online and synchronously. The results showed that the participant demonstrated an increased repertoire of target behaviors related to the development of each document. Additionally, social validity was established through the other participants’ positive evaluations of the importance and feasibility of implementing the documents in school settings. Therefore, it can be concluded that both studies—teacher training on theoretical foundations and collaborative consultation for teachers of students with ASD in regular education—can be effective services for fostering reflection and improving pedagogical practices. However, further research is needed to develop and validate procedures and outcomes, improve working conditions for teachers, and promote legislation that encompasses evidence-based practice in education.
Training and collaborative consultation for teachers in the education of students with Autism Spectrum Disorder
Keywords: Formação de Professores; Consultoria Colaborativa; Análise do Comportamento Aplicada; Transtorno do Espectro Autista; Plano de Ensino Individualizado; Teacher Training; Collaborative Consultation; Applied Behavior Analysis; Autism Spectrum Disorder; Individualized Education Plan; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM::PROGRAMACAO DE CONDICOES DE ENSINO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; 4. Educação de Qualidade; 16. Paz, Justiça e Instituições Eficazes; 17. Parcerias e Meios de Implementação